Phenformin in aqueous co-solvent mixtures of N, N-dimethylformamide, ethanol, N-methylpyrrolidone and dimethyl sulfoxide: Solubility, solvent effect and preferential solvation. (May 2020) - Zhao, Xi; Farajtabar, Ali; Han, Gui; Zhao, Hongkun
Graphic abstract: Highlights: Solubility of phenformin in four co-solvent mixtures was determined and correlated. Solvent effect was studied in terms of solvent-solvent and solute-solvent interactions. Preferential solvation of phenformin in four mixtures were derived through IKBI method. Abstract: The equilibrium mole fraction solubility of phenformin in four co-solvent mixtures of N, N -dimethylformamide (DMF) + water (2), ethanol (1) + water (2) and N -methylpyrrolidone (NMP, 1) + water (2) at temperatures from 278.15 K to 323.15 K and dimethyl sulfoxide (DMSO) (1) + water (2) at temperatures from 293.15 K to 323.15 K were determined via the saturation shake-flask technique. The maximum solubility values were observed in the neat co-solvents of DMF (DMSO, NMP and ethanol). Through the Jouyban-Acree model, the phenformin solubility in the four solvent mixtures was well correlated attaining RAD values less than 3.21% and RMSD values less than 4.84 × 10 −4 . To describe how solvent affect the solubility, the obtained solubility data were introduced into the linear solvation energy relationships model by taking the cavity term and KAT parameters as solvent's descriptors. It was shown that the cavity term and hydrogen bond acidity of solvent play the key role on the solubility variation in aqueous DMF, DMSO, ethanol and NMP mixtures. What's more, the quantitative values for local mole fractions of DMSO (DMF, ethanol or NMP) and water around the drug phenformin were calculated by the Inverse Kirkwood–Buff integrals method based on solubility data. Phenformin was preferentially solvated by water in the DMSO/DMSO (1) + water (2) mixtures with compositions 0 < x 1 < 0.20 and NMP (1) + water (2) mixture with compositions 0 < x 1 < 0.16; while for the ethanol (1) + water (2) mixture with compositions 0.25 < x 1 < 1, phenformin is preferentially solvated ethanol.